Development and characterization of bioplastic composites based on corn starch with different reinforcement materials (Research, Society and Development, 2022)
The use of synthetic polymers as raw material in industry has increased significantly in recent decades, due to the many advantages they have. However, considering the environmental impact that these non-renewable source materials can cause, the search for more sustainable alternatives, such as bioplastics, began. One of these materials is starch, easy to obtain and low cost, however, it has thermal and mechanical properties inferior to polymers. In this sense, this work aims to develop bioplastic starch composites, incorporated with different reinforcement materials, and to evaluate the influence of their addition on the polymer matrix. For this, composites based on corn starch were synthesized through the casting method, incorporated with ZnO, TiO2 and silica. Then, these were characterized by determination of moisture content, tensile and elongation tests, by SEM, FTIR and TGA analysis and soil biodegradation test. The addition of ZnO and TiO2 improved the mechanical properties of the bioplastics, but the silica sample did not obtain good results, as it did not present a good dispersion in the polymer matrix, as could be seen in the morphological analysis. All samples showed similar behavior in the analysis of infrared spectrometry and in terms of thermal stability, however the composite containing ZnO was more stable. In the biodegradation test, the composite with TiO2 showed a behavior more similar to the unfilled bioplastic. Thus, ZnO and TiO2 proved to be interesting as reinforcements to be used in starch bioplastics, especially ZnO, with potential use for several applications.